Three-level inverter-fed model predictive torque control of a permanent magnet synchronous motor with discrete space vector modulation and simplified neutral point voltage balancing - Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (Journal of Power Electronics, 2022)
In this study, discrete space vector modulation (DSVM) is used to achieve the flux and torque ripple reduction of finite set model predictive torque control (FS-MPTC) fed by a three-level neutral point clamped inverter (3L-NPCI). In the proposed DSVM, the synthesis of voltage vectors (VVs) can be controlled and implemented online, thereby eliminating the need for a VV lookup table. In addition, a simple and efficient preselection VV strategy is presented to reduce the number of candidate VVs in the prediction stage. The problem of capacitor voltage imbalance in 3L-NPCI is easily solved without including it as a control objective in the cost function. Thus, the complexity of tuning multiple weighting factors can be reduced. Hence, the proposed PTC-DSVM algorithm is simple and is capable of minimizing torque/flux ripples. It can also achieve a fast torque dynamic performance while maintaining balanced capacitor voltages. The effectiveness of the proposed method is verified through experimental results.
Keywords: Discrete space vector modulation; Flux ripple; Model predictive; Neutral-point clamped inverters; Permanent Magnet Synchronous Motor; Predictive torque controls; Simple++; Three-level neutral point clamped; Three-level neutral point clamped inverte; Voltage vectors; Discrete space vector modulation; Permanent magnet synchronous motor; Predictive torque control; Three-level neutral point clamped inverter